The Role of Human Resource Management in Improving Digital Business Competitiveness - Yulianah, Yulianah; Galuh Boga Kuswara (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rapid development of information technology is driving the emergence of a competitive digital business ecosystem. To survive and thrive in this competition, companies are required to rely not only on technological innovation but also on effective human resource (HR) management. This study aims to analyze the role of human resource management in enhancing digital business competitiveness, specifically through recruitment, competency development, motivation, and performance management. The research method used is a descriptive qualitative approach, with data collection through literature review. The results indicate that human resource management plays a crucial role in enhancing digital business competitiveness through various strategies, ranging from digital talent recruitment, training and competency development, motivation and reward systems, to managing an adaptive work culture. Furthermore, employee retention and career development have proven to be key factors in maintaining the sustainability of digital talent amidst intense competition. The use of technologies such as HRIS, big data, and artificial intelligence also makes HR management more efficient, enabling companies to increase productivity while strengthening their competitive advantage in the digital era.